Resveratrol improves cardiac function and exercise performance in MI-induced heart failure through the inhibition of cardiotoxic HETE metabolites. (December 2018) - Matsumura, Nobutoshi; Takahara, Shingo; Maayah, Zaid H.; Parajuli, Nirmal; Byrne, Nikole J.; Shoieb, Sherif M.; Soltys, Carrie-Lynn M.; Beker, Donna L.; Masson, Grant; El-Kadi, Ayman O.S.; Dyck, Jason R.B.
Abstract: Numerous epidemiological studies have demonstrated that approximately 40% of myocardial infarctions (MI) are associated with heart failure (HF). Resveratrol, a naturally occurring polyphenol, has been shown to be beneficial in the treatment of MI-induced HF in rodent models. However, the mechanism responsible for the effects of resveratrol are poorly understood. Interestingly, resveratrol is known to inhibit cytochrome P450 1B1 (CYP1B1) which is involved in the formation of cardiotoxic hydroxyeicosatetraenoic acid (HETE) metabolites. Therefore, we investigated whether resveratrol could improve MI-induced cardiac remodeling and HF in rats through the inhibition of CYP1B1 and its metabolites. To do this, rats were subjected to either sham surgery or a surgery to ligate the left anterior descending artery to induce a MI and subsequent HF. Three weeks post-surgery, rats with established HF were treated with control diet or administered a diet containing low dose of resveratrol. Our results showed that low dose resveratrol treatment significantly improves % ejection fraction in MI rats and reduces MI-induced left ventricular and atrial remodeling. Furthermore, non-cardiac symptoms of HF such as reduced physical activity improved with low dose resveratrol treatment. Mechanistically, low dose resveratrol treatment of rats with established HF restored levels of fatty acid oxidation and significantly improved cardiac energy metabolism as well as significantly inhibited CYP1B1 and cardiotoxic HETE metabolites induced in MI rats. Overall, the present work provides evidence that low dose resveratrol reduces the severity of MI-induced HF, at least in part, through the inhibition of CYP1B1 and cardiotoxic HETE metabolites.